Metaverse And Hajj: The Meaning Of Muslims In Indonesia - Fernando, Henky; Larasati, Yuniar Galuh (LPPM IAIN Parepare, 2022)
This study describes and explains the meaning of Muslims in Indonesia in the discourse of the pilgrimage through the metaverse space. The description in this study will provide a more comprehensive discussion of the discourse of the pilgrimage through metaverse in the meaning of Muslims in Indonesia. This study uses a virtual ethnographic method, which emphasizes data collection through reading online news texts through the Google search engine using the search keyword “Wacana Ibadah Haji melalui Metaverse